War of Conquest and Defensive War in the Hungarian Thirteenth Century Legislation and the European Ius Commune - Péter Bónis (Journal on European History of Law, 2024)
There are some provisions on the vassal’s obligation to respond to the king’s call to arms in the 13th century Hungarian legislation. In this paper we aim to compare the Hungarian legislation with the European ius commune on this subject, and we try to elucidate which were the sources of the Hungarian legislation in this regard. However, since these provisions are closely linked to the concept of just war, we look at what was considered a just war in the Middle Ages and what the implications of this classification were for the obligations of the vassals. After thorough analysis of the sources, the author made the cautious assumption that the Summa iuris feudorum of Jacobus de Ardizone was presumably the most important source of the Hungarian legislation on this issue of the feudal law.